Matching energy levels between TiO2 and α-Fe2O3 in a core–shell nanoparticle for visible-light photocatalysis. Issue 28 (28th July 2015) - Lin, Zhaoyong; Liu, Pu; Yan, Jiahao; Yang, Guowei
<x xml:space="preserve">Abstract</x> Coupling TiO2 with other semiconductors is a route to extend the optical response range of TiO2 and to improve the efficiency of its photon quantum.